Роль смарт-девайсів у підвищенні обсягів продажів продукції - Юрченко, В. Ю. (ХНУРЕ, 2024)
The value of customers’ and potential customers’ profiles has increased significantly for brands around the world. But most of the tools that cope with collecting such information today are aimed at digital services, such as Internet requests or online purchases. There is still a lot of valuable information that brands can collect from physical customers that remains untracked. The negative consequences of this are partly reflected in the growth of e-commerce, whose global volume is projected to increase by 39% over the next 3 years. This research was conducted to learn methods and mathematical models of collecting information not only for digital services, but also for goods that we can find on the shelves of physical stores.
Keywords: смарт-девайс; маркетинг